2006
DOI: 10.1111/j.1745-7254.2006.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and biodistribution of polymeric micelles of paclitaxel with Pluronic P1231

Abstract: Polymeric micelles using Pluronic P123 can effectively solubilize PTX, prolong blood circulation time and modify the biodistribution of PTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…PEG-bpoly(alkyl acrylate-co-methacrylic acid) micelles entrapping fenofibrate exhibited enhanced oral bioavailability as compared to fenofibrate suspension [261]. Han et al studied the pharmacokinetics and biodistribution of Pluronic P123 micelles loaded with paclitaxel [262]. The effective solubilization of paclitaxel by the micellar core resulted in an increased bioavailability of the drug.…”
Section: F127mentioning
confidence: 99%
“…PEG-bpoly(alkyl acrylate-co-methacrylic acid) micelles entrapping fenofibrate exhibited enhanced oral bioavailability as compared to fenofibrate suspension [261]. Han et al studied the pharmacokinetics and biodistribution of Pluronic P123 micelles loaded with paclitaxel [262]. The effective solubilization of paclitaxel by the micellar core resulted in an increased bioavailability of the drug.…”
Section: F127mentioning
confidence: 99%
“…Illum et al demonstrated that it was possible to signiˆcantly alter the in vitro interaction with isolated macrophages and the biodistribution of model polystyrene nanospheres after coating the particle surface with a Pluronic. 9,10) Additionally, we also reported that PTX-loaded Pluronic P123 micelles could eŠectively prolong blood circulation time and modify the biodistribution of PTX in vivo 11) and exert higher cytotoxicity against resistant human ovarian tumor cell line, SKOV-3/ PTX (unpublished data). Previously, we have reported on micellar PTX formulation employing Pluronic P105, and have demonstrated that the micellar PTX could increase the cytotoxicity against MCF-7/ADR, resistant breast tumor cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PMs possess higher drug loading capacity, significantly lower critical micelle concentration values and greater thermodynamic stability than those of low-molecular weight surfactants micelles (Nishiyama & Kataoka, 2006). And the simple preparation process without organic solvents is also one of the important advantages of PMs (Han et al, 2006). Methoxypolyethylenelglycol-distearyl phosphatidyl-ethanolamine (mPEG-DSPE) is generally used to prepare liposomes.…”
Section: Introductionmentioning
confidence: 99%